(untitled) (Eurasian Medical Research Periodical, 2023)
Pulmonary tuberculosis often develops against the background of diseases that lead to dysfunction of organs and systems, and in a joint course, they have a mutually aggravating interaction. This complicates the timely diagnosis of tuberculosis, and in the treatment entails forced polypharmacy, the development of drug complications and failures in treatment.